Chondroitin sulfate-chitosan nanoparticles for ocular delivery of bromfenac sodium: Improved permeation, retention, and penetration - Abdullah, Tara Abdulrahman; Ibrahim, Naz Jamal; Warsi, Musarrat Husain (International Journal of Pharmaceutical Investigation)
Introduction: Superiority of topical instillation of drug into the cul-de-sac for the treatment of various ophthalmic complications can be validated with commercial availability of a large number of conventional formulations even though this mode of instillation still elicits limitations owing to poor ocular bioavailability. To overcome the drawbacks of conventional formulations, a large number of novel carriers have been investigated. In this perspective, a new novel nanocarrier, chondroitin sulfate (ChS)-chitosan (CS)-nanoparticles (NPs) are being evaluated for improved delivery of bromfenac sodium. Materials and Methods: Formulation was developed and optimized for CS, chondroitin, and initial drug concentration. Optimized formulation was evaluated for various in vitro aspects i.e., particles’ size, size distribution, zeta potential, shape and morphology, in vitro release profile, corneal permeation, corneal retention, corneal uptake, and ocular tolerance test. Results: The mean particle size, polydispersity index, zeta potential, and entrapment efficiency of optimized formulation were found to be 245.6 ± 14.22 nm, 0.187 ± 0.016, +37.59 ± 4.05 mV, and 71.72 ± 4.43%, respectively. Transmission electron microscopic analysis revealed a spherical shape of developed formulation. Further, formulation exhibited biphasic release profile and Korsmeyer–Peppas model was found to be the best fit model. Significantly high transcorneal permeation (1.62-fold) and corneal retention (1.92-fold) of bromfenac was observed through ChS-CS-NPs when compared with marketed eyedrops (P < 0.01). Furthermore, high corneal uptake of CHS CS-NPs was confirmed by confocal laser scanning microscopy (CLSM). Safety profile of the developed formulation was established by hen’s egg test-chorioallantoic membrane test. Conclusion: Encouraging outcomes of in vitro and ex vivo studies indicated that CHS-CS-NPs could be a potential substitute for improved ocular delivery.
Keywords: Bromfenac sodium; chitosan (CS); chondroitin sulfate (ChS); nanoparticles (NPs); ocular delivery; ocular drug delivery; transcorneal permeation